A few remarks on state compensation to victims of crime - Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
This article presents selected issues concerning state compensation to victims of certain offences. The fundamental principles underlying the system of assistance provided to the victims of prohibited acts were discussed, as well as amendments made thereto. Attention was primarily focused on the amendments introduced by the Amending Act of 5 August 2015. These concerned aspects such as persons eligible, scope of compensation and procedures for application review, which were analysed both by legal scholars and practitioners. It has been concluded that the amendments to a large extent eliminated the weaknesses of the previously existing regulations and thus created conditions for basic victim support.
Keywords: odszkodowanie państwowe; ofiara; strona pokrzywdzona; czyn zabroniony; naprawienie szkody